PANDANGAN PIMPINAN GEREJA TENTANG PENGATURAN ORGANISASI GEREJA DI PROVINSI JAWA BARAT - Reslawaty Reslawaty (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
The aim of this qualitative study is to determine the views of church leaders in West Java about 1) the church organization/denomination regulations issued by the Director General of Christian Guidance; 2) the policy of West Java’s Ministry of Religious Affairs on which church organization/denomination regulations were valid at the time; and how church leaders themselves could ensure peace and harmony with the increasing number of new denominations seeking legal status. The study concludes that almost all church leaders were not aware of any of the moratoriums issued by the Director General of Christian Guidance. Church leaders also were critical towards the content of the moratorium, arguing that the government should not restrict any denomination seeking to would establish new churches if they met the requirements set out by the Director General of Christian Guidance.